1997
DOI: 10.1177/096914139700400304
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for Tay-Sachs and Sandhoff Diseases among Massachusetts Residents with French Canadian Background

Abstract: Simultaneous screening for TSD and Sandhoff disease heterozygosity by assay of beta hexosaminidases A and B activities provides a possible method for use with subjects of French Canadian background. The relevance of some of the novel mutations identified in this group needs further study. However, the comparatively high combined frequency of TSD and Sandhoff disease heterozygosity indicates a need for discussion regarding the appropriateness of carrier testing for these disorders for persons of French Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Individuals who were pregnant, had both Ashkenazi Jewish and French Canadian heritage, or indicated that they had a relative who was a carrier for or had TSD, were excluded from the study. The questionnaire used to identify appropriate study participants was previously published (8 ).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals who were pregnant, had both Ashkenazi Jewish and French Canadian heritage, or indicated that they had a relative who was a carrier for or had TSD, were excluded from the study. The questionnaire used to identify appropriate study participants was previously published (8 ).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…The percentages of serum HEXA activity used to identify heterozygotes and non-carriers for TSD were as reported previously (8 ). The diagnostic criteria for serum HEXA used to establish a diagnosis of heterozygosity and non-carrier status for TSD were: carrier, Յ55% HEXA and non-carrier, Ն61% HEXA.…”
Section: Enzyme Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Natowicz, 1997). A recruitment bias may have been present as the individuals tested were volunteers.…”
mentioning
confidence: 99%